Kinesiophobia and its association with balance and mobility in knee osteoarthritis patients in Rawalpindi & Islamabad - Saman Shaukat, Maheen Mazhar, Maria Javed, Maryam Naeem, Aamer Naeem, Shoaib Kayani (Journal of Rawalpindi Medical College, 2021)
Objective: The purpose of this study was to evaluate the relationship of fear avoidance belief or kinesiophobia with balance and mobility in knee osteoarthritis patients. Materials and methods: This cross-sectional correlational study was conducted in Fauji Foundation Hospital, Benazir Bhutto Hospital and Holy Family Hospital, Rawalpindi/Islamabad from January 2019 to June 2019. A total of 64 knee osteoarthritis patients (both male and female) between the ages of 40- 60 years were included in this study. They were selected using the Kallgren Lawrence Classification system (Grade I, II and III) and American College of Rheumatology criteria. Fear avoidance belief questionnaire was used to identify fear avoidance belief/kinesiophobia, Step-up test and Functional Reach test were used to measure balance and timed up and go test was used to measure mobility. Statistical analysis was carried out using SPSS version 21. Kolmogorov-Smirnov test was applied to find out the normal distribution. The relationship between fear avoidance belief and balance and mobility was examined using Spearman’s test of correlation. Results: Results showed a weak negative correlation between fear avoidance belief and functional reach test (r= -0.259, P= 0.039), and a weak positive correlation between fear avoidance belief and timed up and go test (r= 0.26, P= 0.841). Conclusion: Balance and mobility are negatively affected by fear avoidance beliefs in knee osteoarthritic patients. Thus, fear avoidance belief is an important psychological construct to be considered in the assessment and treatment of knee osteoarthritic patients to prevent balance impairments and fall risk.